Il San Matteo di Pisa: un “modello” tra i musei italiani - Giusti, Francesca (Opus Incertum, 2023)
The story of the Civic Museum of Pisa, built by Piero Sanpaolesi in the former convent of San Matteo, and inaugurated in 1949 in the midst of the emergency of reconstruction, intertwines the themes of restoration and museography, representing a significant synthesis of the international debate on culture and museum practice. In this sense, the contribution aims to demonstrate the principle of unity between architectural structure and pieces of art that underlies the project of the museum of San Matteo, where the intent of Sanpaolesi to think the restoration of the building and the exhibition as a whole emerges clearly. Restoration as an opportunity to know the historical and artistic palimpsest that is part of the process of musealization of the building, in relation to an idea of ‘modernity’ compatible with the cultural values of which the building itself is the bearer. Where the idea of valorization acquires meaning not so much because the building ‘contains’ works of art, but because the same operation of rereading the historical narrative of the building is an integral part of the exhibition.